Belize : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses three important sectors of Belize economy: financial, sugar market, and energy. Belize's banking system has continued to strengthen since the 2014 Article IV Consultation in June 2014. Despite recent improvements, some banks' balance sheets are still weak and exposed to adverse macroeconomic developments. The sugar sector makes a very important contribution to Belize's economy. The sector is estimated to account for about 4-5 percent of GDP, 9-10 percent of total exports, 8 percent of employment, and 5-6 percent of foreign exchange earnings. But the reform of EU sugar regime, scheduled to take full effect in 2017, will most likely cause a significant drop in the EU sugar price.